ITPRs/inositol 1,4,5-trisphosphate receptors in autophagy: From enemy to ally - Decuypere, Jean-Paul (Autophagy, 2015)
ITPRs (inositol 1,4,5-trisphosphate receptors), the main endoplasmic reticulum (ER) Ca(2+)-release channels, were originally proposed as suppressors of autophagy. Yet, new evidence has accumulated over recent years supporting a crucial, stimulatory role for ITPRs in driving the autophagic flux. Here, we provide an integrated view on how ITPR-mediated Ca(2+) signaling can have a dual impact on autophagy, depending on the characteristics of the spatio-temporal Ca(2+) signals, including the existence of ER-mitochondrial and ER-lysosomal Ca(2+) signaling microdomains.